Using creativity and the arts to promote mental health in youth living with HIV in South Africa - Jacqueline Hoare; Rebecca Sher; Kathryn R. Cullen (Southern African Journal of HIV Medicine)
Access to adolescent-friendly, culturally relevant and stigma-free mental health support is essential for reducing the long-term psychological, social and economic challenges of mental illness of youth living with HIV (YLWH). Now more than ever, innovative task-shifting interventions, through which non-mental health professionals provide mental health support to YLWH, need to be explored and supported. While many of these have considered shifting tasks to nurses, tapping into the wisdom and inspiration from artists in the community where YLWH are living could represent a novel and potentially powerful task-shifting strategy.